EVALUASI GROUTING PADA SECTION RETAINING WALL – B (DOWNSTREAM) DI KALI SEMARANG, KELURAHAN PANGGUNG LOR, KOTA SEMARANG, JAWA TENGAH - Khalaksita Amikani Asbella; Dwiyanto Joko Suprapto; Fahrudin Fahrudin; Citra Ningtyas (Program Studi Teknik Geologi, Fakultas Teknik, Universitas Diponegoro, 2014)
Kali Semarang is one of the watering pattern that was in Semarang, Central Java, which runs from Pandanaran heading north toward the Java Sea. At the time of Semarang and surrounding areas have a condition that there are no rocks exposed at the surface because it is an area of older alluvium and river stage consisting of loose material such as clay, so this area has soft soil conditions until very soft. Lowering occurs in the area of construction of the embankment caused by the soft soil in the area around the construction of the embankment. Judging from the condition of the soil is soft and very soft, so we must be careful in determining the appropriate and correct methods for prevention of ground movement. Based on the soil conditions in the area of Kali Semarang, a study was undertaken using data SPT (Standard Penetration Test) to see the condition of the soil strength, and then to increase the strength of the soil used a method which is the method of grouting.From the results of drilling conducted at the Gate House point E1 +10 m, known at depth 0-2 m of sand sized loose gravel gray. At a depth of 2-20 m in the form of clay sized soft to very soft with gray. From SPT test data at Gate House point E1 +10 m, obtained N - SPT values <2 (very soft) at a depth of 2.8 to 5.8 m and a depth of 10.4 to 11.7 m. 2-3 N - SPT values (soft) is at a depth of 7.8 to 8.8 m and a depth of 13.4 to 19.3 m. SPT N - values (very dust) contained in an area close to the surface that is at a depth of 1.4 m.Once implemented method of grouting on Retaining Wall section B point 13 +1 m, +2 m point C10, and C18 +2 m point, a change in the value of the SPT test that the higher the value of N-SPT 4 (very dust) its value changed to 10 -15 (rather dense). N-SPT value of 0-1 (very soft), and the N-SPT values 2-3 (soft) turned into a N-SPT values 3-4 (soft), the value of N-SPT 5-7 (firm,) and N-SPT values 8-13 (stiff). To pile foundation bearing capacity changes from 16.57 tons to 35,98 tons to 53,03 tons. From the results of this investigation obtained good results for the purpose of grouting method successfully to increase the carrying capacity of the soil at the study site.Judging from its success with the implementation of the construction of grouting method can be resumed because the carrying capacity of the land has allowed it to withstand the load of the building to be erected.